Environmental psychology : an introduction - 4 0 16; Steg, Linda.;Berg, Agnes E. van den,;de Groot, Judith I. M.; 5 (Chichester, West Sussex, UK : BPS-Blackwell, 2012)
Explores the environment's effects on human wellbeing and behaviour, factors influencing environmental behaviour and ways of encouraging pro-environmental action--
Includes index.
Keywords: 2 -- 0; 6; Environmental psychology. -- 20; 20; 2